2000
DOI: 10.1016/s0921-4534(00)00397-x
|View full text |Cite
|
Sign up to set email alerts
|

D-XY critical behavior in cuprate superconductors

Abstract: We outline the universal and finite temperature critical properties of the 3D-XY model, extended to anisotropic extreme type-II superconductors, as well as the universal quantum critical properties in 2D. On this basis we review: (i) the mounting evidence for 3D-XY behavior in optimally doped cuprate superconductors and the 3D to 2D crossover in the underdoped regime; (ii) the finite size limitations imposed by inhomogeneities; (iii) the experimental evidence for a 2D-XY quantum critical point in the underdope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Noting that in cuprate and amorphous conventional superconductors the spatial extent of the homogeneous domains is limited, 8,[16][17][18][19][20][21][22] we explored the applicability of the 0D-model, neglecting thermal fluctuations, to describe the isothermal magnetization and Nernst signal curves above T c . Sufficiently above T c we observed that for both models, the full 0D-model and its Gaussian version, describe the essential features of the curves, including the temperature dependence of the minimum in the magnetization and maximum in the Nernst signal curves at H m , rather well.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noting that in cuprate and amorphous conventional superconductors the spatial extent of the homogeneous domains is limited, 8,[16][17][18][19][20][21][22] we explored the applicability of the 0D-model, neglecting thermal fluctuations, to describe the isothermal magnetization and Nernst signal curves above T c . Sufficiently above T c we observed that for both models, the full 0D-model and its Gaussian version, describe the essential features of the curves, including the temperature dependence of the minimum in the magnetization and maximum in the Nernst signal curves at H m , rather well.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] On the other hand, there is considerable evidence that cuprate and amorphous conventional superconductors are homogeneous over a limited spatial domain only. 8,[16][17][18][19][20][21][22] In this case, the growth of the correlation lengths is limited by approaching the transition temperature T c because it cannot exceed the respective extent of the homogenous domains. Within a two dimensional superconductor, consisting of a stack of superconducting layers with insulating spacing sheets in between, the adoption of this scenario where the magnetization stems from homogeneous domains with limited extent only would result in an effective 0D-superconductor.…”
mentioning
confidence: 99%
“…Allele frequencies were calculated for each locus separately and the extent of intra-and intersample genetic diversity was estimated using: (i) number of alleles (N a ) per locus; (ii) the observed heterozygosity (H O ); and (iii) expected heterozygosity 1 1 2 1 3 4 1 3 4 (H E ); H O and H E were calculated for each locus, both individually for each sample and across all samples, using the program populations Version 1.2.28 (Langella 2002). Every sample (males and females separately) was then tested (1000 iterations) for deviation from Hardy-Weinberg equilibrium (HWE) across each locus using a modification of the Guo & Thompson (1992) Markov-chain random walk algorithm available in arlequin Version 2.000 (Schneider et al 2000). The statistical significance of deviations from Hardy-Weinberg expectations was adjusted by a sequential Bonferroni correction (Rice 1989) to maintain a type-I error rate of α = 0.05 within each sample.…”
Section: Discussionmentioning
confidence: 99%
“…We also indicate whether the function A max (λ) is increasing or decreasing in each interval. From the table we see that the function A max (λ) is minimized for λ = λ (123) (23) . Thus we have…”
Section: B Calculating the Lieb-robinson Speedmentioning
confidence: 99%
“…This model is well understood and is studied mainly in connection with quantum phase transitions. This model is also of practical interest, for example, in understanding the isolator-superconductor phase transition in cuprate type II superconductors [23]. At zero temperature the system exhibits two phases, one with an energy gap and another which is gapless.…”
Section: Example: Xy-modelmentioning
confidence: 99%